Reliability of shoulder abduction muscle endurance measured using isokinetic dynamometry - Micheletti, J. K. [UNESP]; Andersen, L. L.; Machado, A. F.; Lopes, J. S.S.; Souto, L. R.; Pastre, C. M. [UNESP] (Elsevier, 2021)
Objective: To evaluate reliability of performance and metabolic expenditure during a shoulder abduction endurance test with isokinetic dynamometer. Methods: A total of 28 healthy adults participated in 4 sessions (Orientation, Familiarization, Test and Retest). The muscle endurance test was performed using 50% of the individual maximal isometric voluntary contraction strength (21.9 ± 5.8 Nm). Participants performed repeated 0–90° shoulder abductions until exhaustion in the isokinetic dynamometer at a velocity of 60°/s. Values of time, repetition, rhythm and total work were analyzed. Results: For test and retest, respectively, time to fatigue (seconds) was 95.5 ± 37.6 and 91.1 ± 32.8 (P = 0.27), and repetitions were 31.4 ± 12.1 and 29.9 ± 10.6 (P = 0.23). Reliability was satisfactory [Time: ICC = 0.83 (95% CI = 0.66; 0.92); Repetition: ICC = 0.83 (95% CI = 0. 67; 0.92); Rhythm: ICC = 0.55 (95% CI = 0.24; 0.77); Total work: ICC = 0.85 (95% CI = 0.69; 0.93)]. Conclusion: The isokinetic test for shoulder muscle endurance at 50% of maximal muscle strength has good reliability.
Évaluation de la fiabilité de la mesure d'endurance musculaire de l'abduction de l’épaule à l'aide d'un dynamomètre isocinétique
Keywords: Fatigue; Muscle strength dynamometer; Reproducibility of results; Resistance training